Cork Boiling Wastewater Treatment in Pilot Constructed Wetlands - Gomes, A.C. (2018)
most studies published on the topic of cork boiling wastewater (CBW) treatment or valorization used physico-chemical treatment options rather than biological processes. However, the related costs are high and above those of the biological treatment alternative for wastewaters with similar organic loads but from different sources. Thus, con- structed wetland systems (CWs) can be an alternative to conventional biological treatment systems, namely to activated sludge systems, with the prominent virtues of low construction and operation costs. Until today, there is no study or research published for the treatment of CBW using CW systems. Thus, this investigation is a novelty and included the monitoring over a period of four years of the operation of a horizontal subsurface flow constructed wetland (HSF CW) microcosm-scale system planted with common reeds (Phragmites australis) and filled with light expanded clay aggregates (LECA), as support media for the plants and for biofilm development. The contribution of plants to the treatment was assessed by the comparison with an identical wetland unit without plantation (control bed). After this extended period of operation intended to maximize biomass development and acclimatization, which included stepwise increase of the organic load rate (OLR) up to 8.9 g COD/m2/d, the assessment of the treatment capacity of the system was done by doubling the OLR to 16.4 g COD/m2/d during 200 days.